Memecylon royenii Blume (Melastomataceae) : A New Record for India - Rajendraprasad, M.; Prathapan, S. L.; Pandurangan, A. G.; Shaju, T. (Indian Forester, 2006)
Memecylon royenii Blume, a Sri Lankan element, is recorded for the first time from India. Detailed description with illustration and notes are provided based on fresh collections. Its phytogeographical significance from conservation point of view is also discussed.